2017
DOI: 10.2298/sarh160809148s
|View full text |Cite
|
Sign up to set email alerts
|

Association of alpha-1 antitrypsin level and lung function in patients with chronic obstructive pulmonary disease

Abstract: Introduction/Objective Alpha-1 antitrypsin deficiency is a well established inherited risk factor for chronic obstructive pulmonary disease (COPD); however, alpha-1 antitrypsin level may result in different lung function reduction. The aim of our study was to evaluate possible associations of alpha-1 antitrypsin level and lung function in COPD patients with different alpha-1 antitrypsin phenotypes. Methods Serum alpha-1 antitrypsin concentration from patients (n = 1,167) with COPD, defined according to the GOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a study shows, on Association of alpha-1 antitrypsin level and lung function in patients with chronic obstructive pulmonary disease showed that circulating AAT inversely correlated with FEV1 in COPD cases without AAT deficiency. 24 SAPALDIA project investigated associations of circulating AAT level with lung function in general population and detected negative correlation of serum AAT concentration with FEV1. The amount of AAT that passively diffuses from the serum to the lung increases during an inflammation, which may be present in COPD.…”
Section: Resultsmentioning
confidence: 99%
“…In a study shows, on Association of alpha-1 antitrypsin level and lung function in patients with chronic obstructive pulmonary disease showed that circulating AAT inversely correlated with FEV1 in COPD cases without AAT deficiency. 24 SAPALDIA project investigated associations of circulating AAT level with lung function in general population and detected negative correlation of serum AAT concentration with FEV1. The amount of AAT that passively diffuses from the serum to the lung increases during an inflammation, which may be present in COPD.…”
Section: Resultsmentioning
confidence: 99%